Exploring Elementary School Students’ Critical Thinking Skills through the Student Question-Have Method Assisted by Scrapbook Media - Pramusinta, Yulia; Dewi Maysaroh Tunggil Saputri (Jurnal Ilmiah Sekolah Dasar, 2025)
Critical thinking skills among elementary school students remain suboptimal. One contributing factor is the continued use of conventional teaching methods, which tend to focus more on delivering information than engaging students in analytical and evaluative thinking processes. This study aimed to examine the effect of the Student Question Have method assisted by scrapbook media on students' critical thinking skills in learning Islamic cultural history. The scrapbook media was designed attractively, containing summarized learning materials to enhance student engagement and comprehension. A quantitative approach with a one-group pre-test post-test experimental design was used. The research subjects were third-grade elementary school students. Instruments included a validated critical thinking test and a learning module reviewed by instructional experts. Data were collected through observations, interviews, and critical thinking pre-test and post-test items. Data analysis employed the Wilcoxon signed-rank test. The findings indicated a significant effect of the Student Question Have method supported by scrapbook media on students' critical thinking skills, with a Z score of -2.402 and a significance level of 0.000. These results suggest that incorporating oral and written questioning strategies effectively fosters students’ critical thinking development. The implication of this study highlights the importance of implementing innovative methods and media to enhance the quality of students’ cognitive processes in elementary education.